2021
DOI: 10.1186/s42523-021-00155-8
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities and limits for using the gut microbiome to improve captive animal health

Abstract: Because of its potential to modulate host health, the gut microbiome of captive animals has become an increasingly important area of research. In this paper, we review the current literature comparing the gut microbiomes of wild and captive animals, as well as experiments tracking the microbiome when animals are moved between wild and captive environments. As a whole, these studies report highly idiosyncratic results with significant differences in the effect of captivity on the gut microbiome between host spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 143 publications
1
28
0
Order By: Relevance
“…However, anthropogenic influences can erode the host-lineage specificity of gut microbiota through a process of humanization, in which hosts acquire microbiota constituents found in humans ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ). For example, although the specific effects of captivity on microbiota differ among mammalian species (e.g., Houtz et al, 2021 , Alberdi et al, 2021 ; reviewed in Diaz and Reese, 2021 ), several studies have shown that captive mammals harbor gut microbiota constituents abundant in humans but missing from wild-living conspecific populations ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ), suggesting transmission from humans. If host species and microbiota have adapted to one another, disruption and replacement of native microbiota may have adverse consequences for host phenotypes and fitness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, anthropogenic influences can erode the host-lineage specificity of gut microbiota through a process of humanization, in which hosts acquire microbiota constituents found in humans ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ). For example, although the specific effects of captivity on microbiota differ among mammalian species (e.g., Houtz et al, 2021 , Alberdi et al, 2021 ; reviewed in Diaz and Reese, 2021 ), several studies have shown that captive mammals harbor gut microbiota constituents abundant in humans but missing from wild-living conspecific populations ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ), suggesting transmission from humans. If host species and microbiota have adapted to one another, disruption and replacement of native microbiota may have adverse consequences for host phenotypes and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies in germ-free mice have found that mice seeded with non-native microbiota displayed stunted immunological development and growth rates relative to house mice seeded with native, house-mouse microbiota ( Chung et al, 2012 ; Moeller et al, 2019 ) (although certain non-native, e.g., human, gut microbiota have been shown to provide growth and immune benefits to mice relative to other non-native microbiota or the germ-free state; e.g., Turnbaugh et al, 2006 ; Round and Mazmanian, 2010 ). Similarly, disruption of gut microbiota in captive mammals has been implicated in the gastrointestinal disorders often experienced by captive hosts ( Clayton et al, 2016 ; Diaz and Reese, 2021 ; McKenzie et al, 2017 ), and efforts to restore wild microbiota (e.g., through fecal microbiota transplantation) to improve the health of captive animals has seen success in some cases (e.g., Koeppel et al, 2006 ; reviewed in Diaz and Reese, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transferring this model to human studies will prove challenging because of the need to maintain a controlled research diet over the length of the study. The “captive” environment needed to perform research in animals may reduce the diversity of the microbiome by limiting exposure to other mammals and the environment [ 146 ]. Thus, systematic reviews of studies using natural experimental designs on well-defined human sub-populations may yield the best available evidence.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to properly control the intestinal microbiota during livestock breeding. This is evidenced by the growing importance of the gut microbiome in a variety of health-related studies on humans and livestock [ 62 , 63 ]. It is thought that it will be possible to manage the health of livestock more easily by increasing the ratio of beneficial bacteria and lowering the ratio of harmful bacteria in the intestinal microbiome of livestock.…”
Section: Bio-functional Properties Expected Following Insect Meal App...mentioning
confidence: 99%